Menganalisis Employee Engagement pada Generasi Milenial dan Generasi Z dalam Konteks Kerja Hybrid: A Systematic Literature Review - Wilda Shilviyah Andiyanti; Fairuz Meita Aurelia (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
Employee engagement is critical to organizational performance, employee well-being, and long-term sustainability. In hybrid work contexts, generational differences have become increasingly evident, particularly between Generation Y and Generation Z employees. Generation Y tends to emphasize work–life balance, career development, and meaningful collaboration, while Generation Z prioritizes flexibility, job security, digital integration, and the use of technology in the workplace. This study adopts a systematic literature review (SLR) approach by synthesizing findings from various peer-reviewed studies related to employee engagement and hybrid work practices across generations. The review focuses on identifying key factors that influence employee engagement in modern work environments. The results indicate that hybrid work can significantly enhance employee engagement when organizations provide flexibility, autonomy, adequate technological support, professional development opportunities, and fair reward systems. In addition, supportive organizational culture and effective leadership are important in maintaining employee motivation and commitment. However, differences in generational expectations require organizations to implement adaptive managerial strategies, including flexible work policies, personalized communication approaches, and inclusive leadership practices to strengthen employee engagement across different generations in hybrid work settings.